Adoption of Weed Management Practices Among Corn Farmers in Barangay Kitobo, Kitaotao, Bukidnon - Cabunoc, Rechel Abagon; Arriesgado, Gimma Hubaldo; Bacus, Maryjoy Salubo; Pagutayao, Anecil Quijano (International Journal of Research in Interdisciplinary Studies, 2025)
This study focused on the adoption and effects of weeds to the yield of corn farmers in Barangay Kitobo, Kitaotao, Bukidnon. It focuses on controlling weeds and the challenges they encounter while using environmental-friendly ways to control weeds. Descriptive survey approach was used in the study and gathered information from selective corn farmers using surveys questionnaires, field visits, and face to face interviews. Results showed that mostly corn farmers were dependent on the use of herbicides to control weeds, while eco-friendly methods like mulching, crop rotation, and using of machineries were not commonly practiced. The choice of farmers in controlling weeds were greatly affected by financial problems, lack of training, and insufficient man power. Although most farmers in the Barangay were financially capable, the moderate-high expenses of using sustainable methods made it difficult for them to use these practices. The study showed that farmers need more support, like proper training, financial help, and easier access to the tools and resources they need for their work. By addressing these problems, it can help farmers use more sustainable ways to control weeds, which can lead to higher yield and minimal impact to the environment. The findings of this study will help government leaders and agricultural extension workers create programs that support small scale farmers in using sustainable ways to manage weeds.